Market Reactions to Emergency Community Activity Restrictions Policy - Nabila Salsabella; Marlina Widiyanti; Fida Muthia; Isni Andriana (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This research uses the event study method to test the reaction of capital markets before and after the announcement of the Emergency Community Activity Restrictions (PPKM) policy. The observation period includes 7 days before and 7 days after the event. By using purposive sampling method, the research sample amounts to 29 stocks of the hotel, restaurant, and tourism companies listed on the Indonesia Stock Exchange. The hypothesis is tested with Paired Samples T-Test for those with normal distribution and Wilcoxon Signed Ranks Test for those with no normal distribution. The results showed that there was a difference in average trading volume activity. While average abnormal return and average security return variability did not have significant differences around the announcement. This research implies that stock investors need to consider information about government policies or other non-economic events to appropriately sort out relevant information to sell or maintain stocks under the risks and returns expected by investors. Keywords: Abnormal Return, Trading Volume Activity, Security Return Variability, The Emergency PPKM Policy, Event Study